Snow buntings sing individually distinctive songs and show inter-annual variation in song structure - Baldo, Sarah; Mennill, Daniel J.; Guindre-Parker, Sarah; Gilchrist, H. Grant; Love, Oliver P. (The Wilson Journal of Ornithology, 2014)
Birds use song to communicate with conspecifics, and song can influence both intra-sexual competition and inter-sexual mate choice. Some birds produce repertoires consisting of hundreds of songs while others produce a single song type. For species with a single-song repertoire, there are varying levels of inter-individual variation which can be the result of environmental, genetic, and physiological factors. Male Snow Buntings (Plectrophenax nivalis) typically produce a single song type, and while syllable sharing occurs between individuals, many researchers have anecdotally noted the individuality of each male's song. To investigate this long-held assertion, we performed a detailed bioacoustic analysis of male Snow Buntings recorded in the Canadian Arctic. We use canonical discriminant analysis to provide quantitative evidence confirming that male Snow Buntings sing individually distinctive songs. Furthermore, we present the first evidence that some Snow Buntings exhibit inter-annual variation in song structure; while songs remain consistent within each year, two males changed their song type between years. Inter-individual variation in song content can have important behavioral implications, because it facilitates individual recognition and can affect individual fitness. © 2014 by the Wilson Ornithological Society.